Adult dogs are capable of regulating calcium balance, with no adverse effects on health, when fed a high-calcium diet. Issue 9 (23rd June 2017) - Stockman, Jonathan; Watson, Phillip; Gilham, Matthew; Allaway, David; Atwal, Jujhar; Haydock, Richard; Colyer, Alison; Renfrew, Helen; Morris, Penelope J.
Abstract: Although the implications of long-term high Ca intakes have been well documented in growing dogs, the health consequences of Ca excess in adult dogs remain to be established. To evaluate the impact of feeding a diet containing 7·1 g/4184 kJ (1000 kcal) Ca for 40 weeks on Ca balance and health parameters in adult dogs, eighteen neutered adult Labrador Retrievers, (nine males and nine females) aged 2·5–7·4 years were randomised to one of two customised diets for 40 weeks. The diets were manufactured according to similar nutritional specifications, with the exception of Ca and P levels. The diets provided 1·7 and 7·1 g/4184 kJ (1000 kcal) (200(SD 26) and 881(SD 145) mg/kg body weight 0·75 per d, respectively) Ca, respectively, with a Ca:P ratio of 1·6. Clinical examinations, ultrasound scans, radiographs, health parameters, metabolic effects and mineral balance were recorded at baseline and at 8-week intervals throughout the study. Dogs in both groups were healthy throughout the trial without evidence of urinary, renal or orthopaedic disease. In addition, there were no clinically relevant changes in any of the measures made in either group (all P >0·05). The high-Ca diet resulted in a 3·3-fold increase in faecal Ca excretion ( P <0·001), whereas apparent Ca digestibility (%) and net Ca balance (g/d) did not significantly change from baseline or differ between the groups at any time point (both P >0·05). Ca intakes of up to 7·1 g/4184 kJ (1000 kcal) are well tolerated over a period of 40 weeks, with no adverse effects that could be attributed to the diet or to a high mineral intake.